German military reform and European security - Sarotte, Mary Elise (Adelphi paper, 2001)
Since the fall of the Berlin Wall in 1989, the German military (the Bundeswehr) has faced, and mastered, a series of singular situations: unexpected German reunification, the need to absorb the East German People's Army (NVA), and calls for German out-of-area deployments. Yet now the Bundeswehr must surmount another formidable obstacle: reforming itself. The paper explores the context, content and possible consequences of German military reform. Although the government of Gerhard Schroder recognises the need for change, the actual reform process has been powerfully influenced by a combination of financial, political and societal constraints. Germany never stopped prioritising traditional homeland defence and remains deeply committed to conscription. As a result, the reform process to date suggests that Germany will be unable to meet allied expectations in the international struggle against terrorism, let alone its own declaratory commitment to the strengthening of European defence capabilities.